PENGEMBANGAN MEDIA PEMBELAJARAN POP-UP BOOK LITERASI PADA MATERI PLANET KELAS VI SDN 038 MUARA INTAN (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The implementation of this study aims to develop a pop-up book learning media for planetary material for grade VI elementary schools and to determine the feasibility of a pop-up book learning media. This study uses the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The technique in collecting data used is using a questionnaire and testing to grade VI elementary school students. The feasibility of the pop-up book media was obtained from the validation and testing of the media. validation is carried out by material experts and media experts. In this pop-up book media trial, a large group trial was conducted with a total of 16 students. The results showed that the material expert validation carried out in two stages, namely in stage I the material was categorized as quite valid and stage 2 validation was categorized as very valid. In phase I material validation it was categorized as not feasible and phase 2 validation was carried out with a very valid category. The assessment on the teacher's response was categorized as very feasible and the student's response was categorized as very feasible. It can be concluded that the pop-up book media on the planetary material for grade VI elementary school is valid with a very feasible category in the use of learning activities in the classroom, besides that the media can also be used as literacy material to increase students' insight. Key Words: Learning Media; Pop-Up Book Literacy, Planets in the Solar System